A method for preparing a hydrogenation catalyst protective agent

The active metal salt solution was recovered by microwave heating and calcined acid impregnation method, and the ultra-large pore material and laser etching technology were used to prepare an efficient hydrogenation catalyst protection agent, which solved the problems of small pore volume and low phosphorus capacity in the prior art. It achieves efficient phosphorus adsorption and durability.

CN119175115BActive Publication Date: 2025-02-18LINQU HENGHUI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411677107.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The pore volume of existing hydrogenation catalyst protectors is small and single, resulting in low phosphorus capacity, short life, high active metal content, high production cost, and difficult to meet industrial application requirements.

Method used

The active metal salt solution was recovered by microwave heating and calculating acid impregnation method, and a multi-stage porous oleophobic carrier was prepared by using ultra-large porous aluminum hydroxide powder and titanium sulfate powder composite material, combined with CO2 laser etching and carrageenan-styrene composite porous resin. Enhance the ability and reactivity of phosphorus adsorption.

Benefits of technology

The phosphorus-beaming effect and hydrophilic oleophobic ability are improved, and low cost and durability are achieved. The specific surface area, pore volume, water absorption rate and pore volume ratio of the hydrogenation catalyst protector are significantly improved, extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175115B_ABST
    Figure CN119175115B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method of a hydrogenation catalyst protective agent, belongs to the technical field of protective agents, and comprises the following steps: microwave heating and roasting of a waste catalyst, acid impregnation, filtering, adding a sodium carbonate solution, filtering to obtain an active metal salt solution; mixing and stirring aluminum hydroxide powder, titanium sulfate powder, an active metal salt solution, and other additives, kneading and molding after adding an aqueous solution of nickel oxide and / or copper oxide soluble salts, drying, roasting, and obtaining a multi-stage pore oleophobic carrier, and then performing CO2 laser etching on the surface, putting it into an active metal salt solution, ultrasonic, vacuum drying, roasting, putting it into an aqueous solution of nickel oxide and / or copper oxide soluble salts, ultrasonic, vacuum drying, roasting, putting it into a carrageenan-styrene composite porous resin suspension, stirring, vacuum drying, and obtaining a hydrogenation catalyst protective agent. The hydrogenation catalyst protective agent prepared by the present invention has a certain hydrophilic and oleophobic effect while having excellent phosphorus binding ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective agents, and in particular to a method for preparing a protective agent for a hydrogenation catalyst. Background Art

[0002] The corrosion of the atmospheric and vacuum unit is divided into low temperature zone corrosion and high temperature zone corrosion. The high temperature zone corrosion is mainly cyclopentane acid corrosion and high temperature sulfur corrosion. At present, phosphorus corrosion inhibitors are used to react with metal iron to generate oil-insoluble substances, which are adsorbed on the metal surface to form a protective film to isolate the metal from contact with corrosive substances such as cyclopentane acid, or react with cyclopentane acid to generate non-corrosive oil-soluble products, thereby inhibiting cyclopentane acid corrosion and protecting equipment. However, for metal catalysts in hydrogenation reactions, phosphorus and its compounds are catalyst poisons, and are also poisons for sulfide-type hydrogenation catalysts.

[0003] The study found that phosphorus-based high-temperature slow-release agents would cause an increase in the catalyst bed pressure drop in the hydrogenation test device during the hydrogenation of vacuum distillate oil, resulting in a decrease in catalyst activity; in addition, analysis of the pore structure and chemical composition of industrial deactivated hydrogenation catalysts revealed that the enriched phosphorus was mainly deposited on the surface of the catalyst particles, which not only covered the active centers on the catalyst surface, but also blocked the channels for reactants to enter the interior of the catalyst particles, resulting in the inability to effectively utilize the internal activity of the catalyst, thereby causing the catalyst to be overall deactivated.

[0004] Regardless of whether the phosphorus-containing impurities are deposited and cover the catalyst surface, or diffuse into the pores of the catalyst, the result is that the catalyst pores are blocked or the pore size becomes smaller, and the reactants cannot diffuse into the active center of the catalyst; in addition, the phosphorus-containing impurities carried in the crude oil penetrate the protective agent bed and are also deposited on the catalyst, causing more phosphorus-containing impurities to be deposited on the catalyst surface, resulting in the catalyst bed being filled with powder.

[0005] The existing protective agents have small and single pore volumes, resulting in low phosphorus capacity and short lifespan; on the other hand, the proportion of macropores is low, making it difficult to meet industrial application requirements; and as protective agents, they have a high content of active metals and high production costs.

[0006] Therefore, it is necessary to provide a method for preparing a hydrogenation catalyst protective agent to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0007] In view of this, the present invention provides a method for preparing a hydrogenation catalyst protective agent, which can improve the phosphorus binding effect and hydrophilic and oleophobic capabilities while achieving low cost and durability.

[0008] To achieve the above object, the specific scheme of the present invention is as follows: a method for preparing a hydrogenation catalyst protective agent, comprising the following steps:

[0009] S1. After microwave heating and roasting of the spent catalyst containing molybdenum and tungsten, a sulfuric acid solution is added, stirred for leaching, the filtrate is collected by filtration, a sodium carbonate solution is added, stirred, and filtered to recover an active metal salt solution;

[0010] S2, mixing aluminum hydroxide powder, titanium sulfate powder, extrusion aid, active metal salt solution, and pore-enlarging agent, stirring evenly, adding nickel oxide and / or copper oxide soluble salt aqueous solution, kneading into a mold, drying, and calcining to obtain a multi-level pore oleophobic carrier; wherein the aluminum hydroxide powder is ultra-large pore powder;

[0011] S3. After CO2 laser etching on the surface of the multi-level pore oleophobic carrier, it is put into an active metal salt solution, and after ultrasonic treatment, it is vacuum dried and calcined. It is put into an aqueous solution of nickel oxide and / or copper oxide soluble salts, and after ultrasonic treatment, it is vacuum dried and calcined. It is put into a carrageenan-styrene composite porous resin suspension, stirred, and vacuum dried to obtain a hydrogenation catalyst protective agent.

[0012] The present invention recovers molybdate (MoO4) from spent catalyst by microwave heating roasting and acid impregnation. - ) and tungstate (WO4 - ) is used to provide active metal components, and MoO3 and WO3 are formed by calcination to increase the number of active sites. At the same time, the compressive strength of the catalyst protector is enhanced by forming a stable structure, further improving the durability of the hydrogenation catalyst protector; in addition, compared with direct calcination, the microwave heating calcination method can quickly increase the temperature inside the waste hydrogenation catalyst, accelerate the process of chemical reaction, and thus improve the treatment efficiency; and acid impregnation converts the oxides of molybdenum and tungsten into corresponding acid ions, while increasing their solubility; sodium carbonate solution is used to adjust the pH to remove impurities and improve the recovery rate of molybdenum and tungsten elements.

[0013] The present invention utilizes a composite of ultra-large-pore aluminum hydroxide powder and titanium sulfate powder as a base material. In the process of preparing a multi-level pore oleophobic carrier by roasting, ultra-large-pore powder is used to increase the specific surface area, further improve the overall ability to adsorb phosphorus, and increase the amount of attached phosphorus; the mineralized titanium dioxide provides hydrophilicity and oleophobicity to the carrier due to the rich hydroxyl groups on the surface, and the hydroxyl groups can chemically adsorb with phosphate ions or other forms of phosphorus compounds in phosphorus compounds, further improving the phosphorus binding ability; in addition, part of the active metal salt solution and the aqueous solution of nickel oxide and / or copper oxide soluble salts are mixed in the carrier molding process, and these metal oxides can be closely combined with the carrier material during the roasting process to form a more stable crystal structure to improve the anti-scouring ability of the protective agent and extend the service life.

[0014] The present invention performs CO2 laser etching on the surface of a multi-level pore oleophobic carrier and then immerses the carrier in an active metal salt solution and an aqueous solution of a soluble salt of nickel oxide and / or copper oxide. First, laser etching is used to form microgrooves on the aluminum surface to form a concave-convex surface structure, which increases the overall surface area and enables the metal to be better attached to the surface, thereby improving the overall load capacity. Then, a multiple impregnation process is used to achieve a uniform distribution of active metals from the inside to the outside, providing an active metal center, thereby enhancing the adsorption capacity and reaction activity for phosphorus. At the same time, the carrier with a multi-level pore structure has a high specific surface area and abundant pores, making it easier for phosphorus to contact the active metal center, thereby improving the adsorption efficiency.

[0015] The present invention finally prepares the hydrogenation catalyst protective agent by impregnating carrageenan-styrene composite porous resin. The cross-linked network structure of the carrageenan-styrene composite porous resin not only enhances the overall stability, but also provides more adsorption sites for phosphorus impurities. On the other hand, a large number of hydroxyl groups in the carrageenan-styrene complex form hydrogen bonds with water molecules, giving the surface of the hydrogenation catalyst protective agent hydrophilic and oleophobic properties.

[0016] Optionally, in step S1, sodium carbonate solution is added to adjust the pH of the filtrate to 7.0-8.0.

[0017] The present invention adds sodium carbonate solution to make the pH value of the filtrate reach 7.0-8.0. Under neutral to alkaline conditions, impurities such as iron and aluminum will form precipitation, further effectively removing the impurities, thereby improving the recovery rate of molybdenum and tungsten elements.

[0018] Optionally, in step S1, microwave heating and roasting are carried out at a power of 300-750 W, the microwave heating and roasting time is 30 min, the concentration of the sulfuric acid solution is 12%, the stirring leaching temperature is 60° C., the time is 1-3 h, the concentration of the sodium carbonate solution is 5%, the stirring temperature is 80° C., and the time is 20 min.

[0019] Optionally, in step S2, the multi-level pore oleophobic carrier is kneaded and formed, and then extruded into strips at a frequency of 10-25 Hz in a mold with a hole diameter of 3.0-7.0 mm, dried at 120-150° C. for 2-4 hours, and calcined at 850-950° C. for 2-4 hours.

[0020] Optionally, in step S2, the aluminum hydroxide powder is an ultra-large pore powder with a pore volume of 1.3~1.5mL / g, the extrusion aid includes sesbania powder, cellulose, and citric acid monohydrate, the pore expanding agent is a mixture of one or more of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber, the concentration of the aqueous solution of soluble salts of nickel oxide and / or copper oxide is 1%~3%, and the mixing time is 15~20min.

[0021] The present invention uses ultra-large pore powder to provide large pore channels, and uses cheap and easily available fibers (one or a mixture of activated carbon fibers, wood fibers, polylactic acid fibers, and bamboo fibers) as templates for preparing porous materials, and ultimately prepares a multi-level pore carrier with a macropore content of more than 20% and a diameter of more than 500 nm to improve the overall phosphorus adsorption capacity and increase the amount of attached phosphorus.

[0022] Optionally, the carrageenan-styrene composite porous resin suspension in step S3 is prepared by mixing the carrageenan-styrene composite porous resin with deionized water and ultrasonically treating the mixture at 40-80°C for 20-30 min; wherein the carrageenan-styrene composite porous resin is prepared by mixing a carrageenan-styrene complex, dimethanol formal and 1,2-dichloroethane, expanding the mixture for 12 h, introducing nitrogen, adding anhydrous FeCl3, stirring the mixture at 50°C for 2 h, stirring the mixture at 80°C for 10 h, cooling the mixture to room temperature, and washing the mixture with methanol.

[0023] The present invention uses dimethanol formal as a crosslinking agent and 1,2-dichloroethane as a swelling agent to promote the formation of a porous structure, and forms a carrageenan-styrene composite porous resin with a crosslinked network structure under the catalytic action of anhydrous FeCl3; wherein the carrageenan in the carrageenan-styrene composite provides a large number of hydroxyl groups, and the hydroxyl groups can form hydrogen bonds with water molecules, thereby giving the resin hydrophilic and oleophobic properties and being able to interact with phosphate ions in phosphorus compounds through hydrogen bonds or coordination bonds; in addition, the carrageenan-styrene composite porous resin forms a stable three-dimensional network structure to enhance overall stability, and the formation of the porous structure increases its surface area, further providing more adsorption sites for phosphorus impurities.

[0024] Optionally, the carrageenan-styrene complex is prepared by mixing soluble carrageenan with deionized water, mechanically stirring the mixture at 300 rpm at 80°C for 1 hour, adding potassium persulfate, sodium dodecyl sulfate and styrene under a nitrogen atmosphere, polymerizing the mixture at 80°C and stirring the mixture at 300 rpm for 5 hours, cooling the mixture, adding ethanol to precipitate the mixture, washing the mixture, drying the mixture at 60°C for 5 to 10 hours, extracting the mixture with toluene for 5 hours, and drying the mixture at 60°C for 5 to 10 hours; wherein the mass ratio of soluble carrageenan, potassium persulfate, sodium dodecyl sulfate and styrene is 8:1:4:24.

[0025] The present invention uses potassium persulfate as a free radical initiator, and sodium dodecyl sulfate promotes the mixing of an aqueous phase and an organic phase, triggering a polymerization reaction between styrene monomers and free radicals to form polystyrene chains. At the same time, the styrene monomers are mixed with carrageenan to form a grafted polymer, thereby enhancing the stability and hydrophobicity of the material.

[0026] Optionally, in step S3, after the surface of the multi-level pore oleophobic carrier is etched with CO2 laser, it is put into an active metal salt solution, ultrasonically treated for 10 minutes, vacuum dried at 60°C for 2 to 4 hours, calcined at 500 to 800°C for 1 to 4 hours, put into an aqueous solution of nickel oxide and / or copper oxide soluble salts, and the above ultrasonic treatment, vacuum drying and calcination processes are repeated. Finally, it is put into a carrageenan-styrene composite porous resin suspension, stirred for 2 to 4 hours, and vacuum dried at 60°C for 2 to 4 hours to obtain a hydrogenation catalyst protective agent.

[0027] Optionally, the hydrogenation catalyst protective agent comprises the following raw materials in parts by weight: 50 parts of a multi-stage pore oleophobic carrier, 60-100 parts of an active metal salt solution, 30-50 parts of an aqueous solution of a soluble salt of nickel oxide and / or copper oxide, and 100-150 parts of a carrageenan-styrene composite porous resin suspension.

[0028] Optionally, the multi-level pore oleophobic carrier comprises the following raw materials in parts by weight: 100 parts of aluminum hydroxide powder, 5-15 parts of titanium sulfate powder, 5 parts of extrusion aid, 10-20 parts of active metal salt solution, 20-40 parts of pore expander, and 5-10 parts of aqueous solution of soluble salt of nickel oxide and / or copper oxide; the carrageenan-styrene composite porous resin suspension comprises the following raw materials in parts by weight: 40-60 parts of carrageenan-styrene composite porous resin and 60-90 parts of deionized water; wherein, the carrageenan-styrene composite porous resin comprises the following raw materials in parts by weight: 11 parts of carrageenan-styrene complex, 6 parts of dimethanol formal, 80 parts of 1,2-dichloroethane, and 4 parts of anhydrous FeCl3.

[0029] The above technical solution of the present invention includes at least the following beneficial effects:

[0030] 1. The present invention uses a microwave-assisted roasting and acid impregnation method and then uses sodium bicarbonate to remove impurities and recover molybdate (MoO4 - ) and tungstate (WO4 - ) to provide active metal components, improving the treatment efficiency while increasing the content of molybdate (MoO4 - ) and tungstate (WO4 - )'s recovery and purity of active metal salts.

[0031] 2. The present invention utilizes a composite of ultra-large-pore aluminum hydroxide powder and titanium sulfate powder as a base material. The large-pore base material provides a high specific surface area and increases the amount of phosphorus attachment. In addition, the mineralized titanium dioxide provides hydrophilicity and oleophobicity and chemical adsorption of phosphorus compounds, further improving the phosphorus binding capacity. The mixed solution of a portion of active metal salts and an aqueous solution of soluble nickel oxide and / or copper oxide salts allows the metal oxide to be tightly combined with the carrier material during the roasting process, forming a more stable crystal structure to improve the protective agent's anti-scouring ability and extend its service life.

[0032] 3. The present invention uses laser etching to form a concave-convex surface on the surface of the multi-level pore oleophobic carrier to increase the overall specific surface area, and provides active metal centers by impregnating a metal salt solution to enhance the adsorption capacity and reaction activity for phosphorus.

[0033] 4. The present invention finally prepares the hydrogenation catalyst protective agent by impregnating the carrageenan-styrene composite porous resin. The cross-linked network structure of the carrageenan-styrene composite porous resin not only enhances the stability of the overall structure, but also provides more adsorption sites for phosphorus impurities. On the other hand, a large number of hydroxyl groups in the carrageenan-styrene complex endow the surface of the hydrogenation catalyst protective agent with hydrophilic and oleophobic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a physical sample picture of the hydrogenation catalyst protective agent prepared in Example 1 of the present invention;

[0035] Figure 2 This is a scanning electron microscope image of the hydrogenation catalyst protective agent prepared in Example 1 of the present invention;

[0036] Figure 3 This is a scanning electron microscope image of the hydrogenation catalyst protective agent prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0038] Example 1

[0039] 60 parts of spent catalyst containing molybdenum and tungsten were calcined by microwave heating at 550 W for 30 minutes, then added to 120 parts of 12% sulfuric acid solution, stirred and leached at 60°C for 2.5 hours, and the filtrate was collected by filtration. After that, 5% sodium carbonate solution was added to adjust the pH to 7.0, stirred at 80°C for 20 minutes, and filtered to recover the active metal salt solution. 100 parts of aluminum hydroxide powder (ultra-large pore powder with a pore volume of 1.5 mL / g), 10 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 15 parts of an active metal salt solution, and 30 parts of a mixture of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber were mixed and stirred for 15 minutes, and then 8 parts of a 2% mixed aqueous solution of nickel oxide and copper oxide soluble salts were added. The mixture was kneaded until formed and extruded at a frequency of 20 Hz in a mold with a pore diameter of 5.0 mm. The mixture was dried at 140°C for 3 hours and then calcined at 900°C for 3 hours to obtain a multi-pore oleophobic carrier.

[0040] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan under nitrogen atmosphere, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 8 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 8 hours to obtain carrageenan-styrene composite. 11 parts of carrageenan-styrene composite and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, nitrogen was introduced, 4 parts of anhydrous FeCl3 were added, stirred at 50°C for 2 hours, stirred at 80°C for 10 hours at 300 rpm, cooled to room temperature, and the precipitate was washed with methanol until the filtrate became almost colorless to obtain carrageenan-styrene composite porous resin. After adding 80 parts of deionized water to 40 parts of carrageenan-styrene composite porous resin, the suspension of carrageenan-styrene composite porous resin was prepared by ultrasonic treatment at 60° C. for 25 minutes.

[0041] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, they were put into 80 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 2.5 hours, calcined at 600°C for 2 hours, put into 40 parts of a mixed aqueous solution of nickel oxide and copper oxide soluble salts, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 600°C for 2 hours, put into 120 parts of carrageenan-styrene composite porous resin suspensions, stirred for 3 hours, and vacuum dried at 60°C for 3 hours to obtain a hydrogenation catalyst protective agent.

[0042] Example 2

[0043] 75 parts of spent catalyst containing molybdenum and tungsten were calcined by microwave heating at 750 W for 30 minutes, then added to 200 parts of 12% sulfuric acid solution, stirred and leached at 60°C for 2 hours, and the filtrate was collected by filtration. After that, 5% sodium carbonate solution was added to adjust the pH to 7.2, and then stirred at 80°C for 20 minutes, and filtered to recover the active metal salt solution. 100 parts of aluminum hydroxide powder (ultra-large pore powder with a pore volume of 1.5 mL / g), 15 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 20 parts of an active metal salt solution, 40 parts of activated carbon fiber, a mixture of wood fiber, polylactic acid fiber and bamboo fiber were mixed and stirred for 20 minutes, and then 10 parts of a 3% aqueous solution of copper oxide soluble salt were added. The mixture was kneaded until formed and then extruded at a frequency of 5 Hz in a mold with a pore diameter of 7.0 mm. The mixture was dried at 150°C for 4 hours and then calcined at 850°C for 4 hours to obtain a multi-pore oleophobic carrier.

[0044] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; under a nitrogen atmosphere, 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 10 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 10 hours to obtain a carrageenan-styrene complex. 11 parts of carrageenan-styrene complex and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, introduced with nitrogen, added with 4 parts of anhydrous FeCl3, stirred at 50°C for 2 hours, stirred at 80°C at 300 rpm for 10 hours, cooled to room temperature, and washed with methanol until the filtrate became almost colorless to obtain a carrageenan-styrene composite porous resin. 90 parts of deionized water were added to 60 parts of carrageenan-styrene composite porous resin, and then ultrasonically treated at 80°C for 30 minutes to obtain a carrageenan-styrene composite porous resin suspension.

[0045] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, they were put into 100 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 4 hours, calcined at 800°C for 4 hours, put into 50 parts of aqueous solutions of nickel oxide and / or copper oxide soluble salts, ultrasonically treated for 10 minutes, vacuum dried for 4 hours, calcined at 800°C for 4 hours, put into 150 parts of carrageenan-styrene composite porous resin suspensions, stirred for 4 hours, and vacuum dried at 60°C for 4 hours to obtain a hydrogenation catalyst protective agent.

[0046] Example 3

[0047] 50 parts of spent catalyst containing molybdenum and tungsten were calcined by microwave heating at 300 W for 30 minutes, and then added to 180 parts of 12% sulfuric acid solution. After stirring and leaching at 60°C for 1.5 hours, the filtrate was collected by filtration, and then a 5% sodium carbonate solution was added to adjust the pH to 8. The mixture was stirred at 80°C for 20 minutes and filtered to recover the active metal salt solution. 100 parts of aluminum hydroxide powder (ultra-large pore powder with a pore volume of 1.3 mL / g), 5 to 15 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 10 parts of an active metal salt solution, and 20 to 40 parts of a mixture of activated carbon fiber and bamboo fiber were mixed and stirred for 15 minutes, and then 5 parts of a 1% aqueous solution of nickel oxide soluble salt were added. The mixture was kneaded until formed and then extruded at a frequency of 10 Hz through a mold with a pore diameter of 3.0 mm. The mixture was dried at 120°C for 2 hours and then calcined at 950°C for 2 hours to obtain a multi-pore oleophobic carrier.

[0048] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; under a nitrogen atmosphere, 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 5 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 5 hours to obtain a carrageenan-styrene complex.

[0049] 11 parts of carrageenan-styrene complex and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, introduced with nitrogen, added with 4 parts of anhydrous FeCl3, stirred at 50°C for 2 hours, stirred at 80°C at 300 rpm for 10 hours, cooled to room temperature, and washed with methanol until the filtrate became almost colorless to obtain a carrageenan-styrene composite porous resin. 60 parts of deionized water were added to 40 parts of carrageenan-styrene composite porous resin, and then ultrasonically treated at 40°C for 20 minutes to obtain a carrageenan-styrene composite porous resin suspension.

[0050] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, the surfaces were put into 60 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 2 hours, calcined at 500°C for 1 hour, put into 30 parts of aqueous solutions of nickel oxide and / or copper oxide soluble salts, ultrasonically treated for 10 minutes, vacuum dried for 2 hours, calcined at 500-800°C for 1 hour, put into 100 parts of carrageenan-styrene composite porous resin suspensions, stirred for 2 hours, and vacuum dried at 60°C for 2 hours to obtain a hydrogenation catalyst protective agent.

[0051] Example 4

[0052] 55 parts of spent catalyst containing molybdenum and tungsten were calcined by microwave heating at 350 W for 30 minutes, then added to 190 parts of 12% sulfuric acid solution, stirred and leached at 60°C for 2 hours, and the filtrate was collected by filtration. After that, 5% sodium carbonate solution was added to adjust the pH to 7.4, and then stirred at 80°C for 20 minutes. The active metal salt solution was recovered by filtration. 100 parts of aluminum hydroxide powder (ultra-large pore powder with a pore volume of 1.4 mL / g), 10 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 15 parts of an active metal salt solution, and 25 parts of a mixture of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber were mixed and stirred for 18 minutes, and then 7 parts of a 2% mixed aqueous solution of nickel oxide and copper oxide soluble salts were added. The mixture was kneaded until formed and extruded at a frequency of 20 Hz in a mold with a pore diameter of 4.0 mm. The mixture was dried at 140°C for 3 hours and then calcined at 900°C for 3.5 hours to obtain a multi-pore oleophobic carrier.

[0053] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; under a nitrogen atmosphere, 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 8 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 8 hours to obtain a carrageenan-styrene complex.

[0054] 11 parts of carrageenan-styrene complex and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, introduced with nitrogen, added with 4 parts of anhydrous FeCl3, stirred at 50°C for 2 hours, stirred at 80°C at 300 rpm for 10 hours, cooled to room temperature, and washed with methanol until the filtrate became almost colorless to obtain a carrageenan-styrene composite porous resin. 70 parts of deionized water were added to 50 parts of carrageenan-styrene composite porous resin, and then ultrasonically treated at 70°C for 25 minutes to obtain a carrageenan-styrene composite porous resin suspension.

[0055] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, they were put into 80 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 600°C for 2 hours, put into 40 parts of a mixed aqueous solution of nickel oxide and copper oxide soluble salts, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 600°C for 2 hours, put into 120 parts of carrageenan-styrene composite porous resin suspensions, stirred for 4 hours, and vacuum dried at 60°C for 3 hours to obtain a hydrogenation catalyst protective agent.

[0056] Example 5

[0057] 70 parts of spent catalyst containing molybdenum and tungsten were heated and calcined by microwave at 650W for 30min, then added to 200 parts of 12% sulfuric acid solution, stirred and leached at 60℃ for 1h, filtered and collected the filtrate, added 5% sodium carbonate solution to adjust the pH to 7.6, stirred at 80℃ for 20min, filtered and recovered to obtain active metal salt solution. 100 parts of aluminum hydroxide powder (ultra-large pore powder with pore volume of 1.5mL / g), 12 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 14 parts of active metal salt solution, and 35 parts of activated carbon fiber were mixed and stirred for 20min, and then 10 parts of 2% aqueous solution of copper oxide soluble salt were added, kneaded to form, extruded into a mold with a pore diameter of 4.0mm at a frequency of 15Hz, dried at 140℃ for 3h, and calcined at 900℃ for 3h to obtain a hierarchical pore oleophobic carrier.

[0058] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan under nitrogen atmosphere, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 8 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 6 hours to obtain a carrageenan-styrene composite. 11 parts of carrageenan-styrene composite and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, nitrogen was introduced, 4 parts of anhydrous FeCl3 were added, stirred at 50°C for 2 hours, stirred at 80°C at 300 rpm for 10 hours, cooled to room temperature, and the precipitate was washed with methanol until the filtrate became almost colorless to obtain a carrageenan-styrene composite porous resin. After adding 80 parts of deionized water to 60 parts of carrageenan-styrene composite porous resin, the suspension of carrageenan-styrene composite porous resin was prepared by ultrasonic treatment at 50° C. for 30 minutes.

[0059] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, they were put into 80 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 700°C for 2.5 hours, put into 40 parts of a mixed aqueous solution of nickel oxide and copper oxide soluble salts, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 700°C for 3 hours, put into 120 parts of carrageenan-styrene composite porous resin suspensions, stirred for 3.5 hours, and vacuum dried at 60°C for 2.5 hours to obtain a hydrogenation catalyst protective agent.

[0060] Example 6

[0061] 65 parts of spent catalyst containing molybdenum and tungsten were calcined by microwave heating at 450 W for 30 minutes, then added to 180 parts of 12% sulfuric acid solution, stirred and leached at 60°C for 3 hours, and the filtrate was collected by filtration. After that, 5% sodium carbonate solution was added to adjust the pH to 7-8, and then stirred at 80°C for 20 minutes, and filtered to recover the active metal salt solution. 100 parts of aluminum hydroxide powder (ultra-large pore powder with a pore volume of 1.4 mL / g), 9 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 15 parts of an active metal salt solution, and 30 parts of a mixture of wood fiber, polylactic acid fiber, and bamboo fiber were mixed and stirred for 20 minutes, and then 10 parts of a 2% aqueous solution of copper oxide soluble salt were added. The mixture was kneaded until formed and then extruded at a frequency of 20 Hz in a mold with a pore diameter of 6.0 mm. The mixture was dried at 130°C for 3 hours and then calcined at 900°C for 3.5 hours to obtain a multi-pore oleophobic carrier.

[0062] 4 parts of soluble carrageenan were added to 80 parts of deionized water, and mechanically stirred at 300 rpm for 1 hour at 80°C to obtain paste carrageenan; 0.5 parts of potassium persulfate, 2 parts of sodium dodecyl sulfate and 12 parts of styrene were added to the paste carrageenan under nitrogen atmosphere, polymerized at 80°C and stirred at 300 rpm for 5 hours, cooled to room temperature, ethanol was added to precipitate the product, washed with ethanol, dried at 60°C for 8 hours, extracted with toluene for 5 hours, and finally dried at 60°C for 9 hours to obtain a carrageenan-styrene composite. 11 parts of carrageenan-styrene composite and 6 parts of dimethanol formal were added to 80 parts of 1,2-dichloroethane, expanded at room temperature for 12 hours, nitrogen was introduced, 4 parts of anhydrous FeCl3 were added, stirred at 50°C for 2 hours, stirred at 80°C at 300 rpm for 10 hours, cooled to room temperature, and the precipitate was washed with methanol until the filtrate became almost colorless to obtain a carrageenan-styrene composite porous resin. After adding 80 parts of deionized water to 50 parts of carrageenan-styrene composite porous resin, the suspension of carrageenan-styrene composite porous resin was prepared by ultrasonic treatment at 70° C. for 30 minutes.

[0063] After CO2 laser etching on the surface of 50 parts of multi-level pore oleophobic carriers, they were put into 60-100 parts of active metal salt solutions, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 600°C for 2 hours, put into 45 parts of nickel oxide soluble salt aqueous solution, ultrasonically treated for 10 minutes, vacuum dried for 3 hours, calcined at 600°C for 2 hours, put into 130 parts of carrageenan-styrene composite porous resin suspension, stirred for 3 hours, and vacuum dried at 60°C for 3 hours to obtain a hydrogenation catalyst protective agent.

[0064] The present invention also carries out comparative examples and related tests.

[0065] Comparative Example 1

[0066] Compared with Example 1, the difference is that titanium sulfate is no longer added as a raw material for preparing a multi-level pore oleophobic carrier and carrageenan-styrene composite porous resin is no longer prepared. The other components and preparation steps are exactly the same, that is, 100 parts of aluminum hydroxide powder (pore volume 1.5 mL / g ultra-large pore powder), 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 15 parts of an active metal salt solution, 30 parts of a mixture of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber are mixed and stirred for 15 minutes, and then 8 parts of a 2% mixed aqueous solution of nickel oxide and copper oxide soluble salts are added. After kneading to form, the mixture is extruded at a frequency of 20 Hz in a mold with a pore diameter of 5.0 mm, dried at 140°C for 3 hours, and calcined at 900°C for 3 hours to obtain a multi-level pore carrier.

[0067] The last step is to carry out CO2 laser etching on the surface of 50 parts of the multi-level porous carrier, put it into 80 parts of active metal salt solution, ultrasonically treat for 10 minutes, vacuum dry for 2.5 hours, calcine at 600°C for 2 hours, put it into 40 parts of a mixed aqueous solution of nickel oxide and copper oxide soluble salts, ultrasonically treat for 10 minutes, vacuum dry for 3 hours, and calcine at 600°C for 2 hours to obtain a hydrogenation catalyst protective agent.

[0068] Comparative Example 2

[0069] Compared with Example 1, the only difference is that microwave-assisted roasting and acid leaching followed by adding sodium carbonate solution to adjust the pH and recover the active metal salt solution is no longer used, but sulfuric acid solution is directly used for leaching and recovery, that is, 60 parts of spent catalyst containing molybdenum and tungsten elements are added to 120 parts of 12% sulfuric acid solution, and after stirring and leaching at 60°C for 2.5 hours, the active metal salt solution is recovered by filtration; the other components and preparation steps are completely the same, and a hydrogenation catalyst protective agent is prepared.

[0070] Comparative Example 3

[0071] Compared with Example 1, the only difference is that the aluminum hydroxide powder no longer uses ultra-large pore powder, that is, 100 parts of aluminum hydroxide powder (pore volume 0.5 mL / g), 10 parts of titanium sulfate powder, 5 parts of sesbania powder, a mixture of cellulose and citric acid monohydrate, 15 parts of an active metal salt solution, and 30 parts of a mixture of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber are mixed and stirred for 15 minutes, and then 8 parts of a mixed aqueous solution of 2% nickel oxide and copper oxide soluble salts are added, and the mixture is kneaded to form and extruded at a frequency of 20 Hz in a mold with a hole diameter of 5.0 mm, and then dried at 140°C for 3 hours and calcined at 900°C for 3 hours to obtain a multi-level pore oleophobic carrier; the other components and preparation steps are exactly the same, and a hydrogenation catalyst protective agent is prepared.

[0072] Comparative Example 4

[0073] Compared with Example 1, the only difference is that CO2 laser etching is no longer used to modify the surface of the multi-level pore oleophobic carrier, that is, 50 parts of the multi-level pore oleophobic carrier are directly put into 80 parts of the active metal salt solution, and the other components and preparation steps are exactly the same to prepare a hydrogenation catalyst protective agent.

[0074] The hydrogenation catalyst protective agents prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to relevant performance tests. According to GB / T44552-2024 particle size distribution determination aerosol particle differential mobility analysis method, HG / T6138-2023 specific surface area and pore size analyzer, GB / T43091-2023 powder compressive strength test method, SH / T0958-2017 molded catalyst and catalyst carrier mechanical vibration bulk density determination method, GB / T14207-2008 sandwich structure or core water absorption test method, the particle size, specific surface area, pore volume, average crushing strength, compacted density, water absorption rate and pore volume ratio were tested respectively, and the test results are shown in Table 1.

[0075] Table 1: Performance test table of hydrogenation catalyst protective agent

[0076]

[0077] As shown in Table 1, the specific surface area, pore volume, water absorption rate and pore volume ratio of >500 nm of the hydrogenation catalyst protective agents prepared in Examples 1 to 6 are significantly higher than those of the hydrogenation catalyst protective agents prepared in Comparative Examples 1 to 4;

[0078] Combined with the data in Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that the addition of titanium sulfate powder and carrageenan-styrene composite porous resin significantly improves the specific surface area, average crushing strength and hydrophilicity of the hydrogenation catalyst protective agent; it can be seen from the comparison between Example 1 and Comparative Example 3 that the ultra-large pore aluminum hydroxide powder significantly increases the pore volume, and the proportion of pore volume >500nm is significantly increased; it can be seen from the comparison between Example 1 and Comparative Example 4 that the average crushing strength of the hydrogenation catalyst protective agent is significantly improved after the protective agent surface is modified by laser etching and then loaded with metal oxide.

[0079] The active metal salts recovered in Examples 1 to 6 and Comparative Examples 1 to 4 were detected and calculated according to the inductively coupled plasma atomic emission spectrometry method for the determination of silicon, iron, phosphorus, boron, chromium, nickel, tungsten, copper, manganese and molybdenum contents in vanadium aluminum alloys of YB / T4908.2-2021. The recovery rates of the metal salt solutions of molybdenum and tungsten elements are shown in Table 2.

[0080] Table 2: Molybdenum and tungsten recovery test table

[0081]

[0082] It can be seen from Table 2 that the recovery rate of the metal salt solution of molybdenum and tungsten elements in Comparative Example 2 is significantly low; combined with the data in Table 2, the recovery rate of the metal salt solution of molybdenum and tungsten elements is significantly improved in the metal salt solution recovered by microwave roasting, acid impregnation and sodium carbonate adjustment to a neutral or alkaline environment.

[0083] The hydrogenation catalyst protective agents prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested on a 300 mL continuous isothermal fixed bed hydrogenation test device. Suizhong 36-1 minus three-line distillate oil was used as the raw oil, to which a phosphorus-based high-temperature corrosion inhibitor with a mass fraction of 0.20% was added. The hydrogenation test device was operated at a system pressure of 3.0 MPa, a reaction temperature of 300 ° C, and a liquid hourly volume space velocity of 1.0 h -1 After running for 72 hours under the condition of hydrogen-to-oil volume ratio of 400:1, the unit was shut down and the hydrogenation catalyst protective agent loaded in the reactor was removed. The phosphorus binding effect of the hydrogenation catalyst protective agent was tested according to the national standard GB / T42513.2-2023 Nickel alloy chemical analysis method Part 2: Determination of phosphorus content using molybdenum blue spectrophotometry. The results are shown in Table 3.

[0084] Table 3: Phosphorus content test results

[0085]

[0086] It can be seen from Table 3 that the phosphorus content of the hydrogenation catalyst protective agent prepared in Examples 1 to 6 is significantly higher than that of the hydrogenation catalyst protective agent prepared in Comparative Examples 1 to 4; it can be seen from the comparison between Example 1 and Comparative Examples 1, 3, and 4 that in Example 1, the use of carrageenan-styrene composite hydrophilic porous resin, ultra-large pore aluminum hydroxide powder and laser etching of the hydrogenation catalyst protective agent significantly improves the amount of bound phosphorus.

[0087] The actual sample of the hydrogenation catalyst protective agent prepared in the final embodiment 1 is as follows Figure 1 The hydrogenation catalyst protective agents prepared in Examples 1 and 2 were tested by scanning electron microscope, and the results were as follows: Figure 2 , 3 shown.

[0088] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a hydrogenation catalyst protective agent, characterized in that: The following steps are involved: S1. After microwave heating and roasting of the spent catalyst containing molybdenum and tungsten, a sulfuric acid solution is added, stirred for leaching, the filtrate is collected by filtration, a sodium carbonate solution is added, stirred, and filtered to recover an active metal salt solution; S2, mixing aluminum hydroxide powder, titanium sulfate powder, extrusion aid, active metal salt solution, and pore-enlarging agent, stirring evenly, adding nickel oxide and / or copper oxide soluble salt aqueous solution, kneading into a mold, drying, and calcining to obtain a multi-level pore oleophobic carrier; wherein the aluminum hydroxide powder is ultra-large pore powder; S3. After CO2 laser etching on the surface of the multi-level pore oleophobic carrier, it is put into an active metal salt solution, and after ultrasonic treatment, it is vacuum dried and calcined. It is put into an aqueous solution of nickel oxide and / or copper oxide soluble salts, and after ultrasonic treatment, it is vacuum dried and calcined. It is put into a carrageenan-styrene composite porous resin suspension, stirred, and vacuum dried to obtain a hydrogenation catalyst protective agent.

2. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: In the step S1, sodium carbonate solution is added to make the pH of the filtrate reach 7.0-8.

0.

3. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: In the step S1, microwave heating and roasting are carried out at a power of 300-750 W, the microwave heating and roasting time is 30 min, the concentration of the sulfuric acid solution is 12%, the stirring leaching temperature is 60° C., the time is 1-3 h, the concentration of the sodium carbonate solution is 5%, the stirring temperature is 80° C., and the time is 20 min.

4. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: In the step S2, the multi-level pore oleophobic carrier is kneaded and formed, and then extruded into strips at a frequency of 10-25 Hz in a mold with a hole diameter of 3.0-7.0 mm, dried at 120-150° C. for 2-4 hours, and calcined at 850-950° C. for 2-4 hours.

5. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: In step S2, the aluminum hydroxide powder is an ultra-large pore powder with a pore volume of 1.3-1.5 mL / g, the extrusion aid includes sesbania powder, cellulose, and citric acid monohydrate, the pore expanding agent is a mixture of one or more of activated carbon fiber, wood fiber, polylactic acid fiber, and bamboo fiber, the concentration of the aqueous solution of soluble salts of nickel oxide and / or copper oxide is 1%-3%, and the mixing time is 15-20 min.

6. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: The carrageenan-styrene composite porous resin suspension in step S3 is prepared by mixing the carrageenan-styrene composite porous resin with deionized water and then ultrasonically treating it at 40-80°C for 20-30 minutes; wherein the carrageenan-styrene composite porous resin is prepared by mixing carrageenan-styrene complex, dimethanol formal and 1,2-dichloroethane and then expanding it for 12 hours, introducing nitrogen, adding anhydrous FeCl3, stirring at 50°C for 2 hours, stirring at 80°C for 10 hours, cooling to room temperature, and washing with methanol.

7. The method for preparing a hydrogenation catalyst protective agent according to claim 6, characterized in that: The carrageenan-styrene composite is prepared by mixing soluble carrageenan with deionized water, mechanically stirring at 300 rpm for 1 hour at 80°C, adding potassium persulfate, sodium dodecyl sulfate and styrene under a nitrogen atmosphere, polymerizing at 80°C and stirring at 300 rpm for 5 hours, cooling, adding ethanol for precipitation, washing, drying at 60°C for 5-10 hours, extracting with toluene for 5 hours, and drying at 60°C for 5-10 hours; wherein the mass ratio of soluble carrageenan, potassium persulfate, sodium dodecyl sulfate and styrene is 8:1:4:

24.

8. The method for preparing a hydrogenation catalyst protective agent according to claim 1, characterized in that: In the step S3, after the surface of the multi-level pore oleophobic carrier is etched with CO2 laser, it is put into an active metal salt solution, ultrasonically treated for 10 minutes, vacuum dried at 60°C for 2-4 hours, calcined at a temperature of 500-800°C for 1-4 hours, put into an aqueous solution of nickel oxide and / or copper oxide soluble salt, and the above ultrasonic treatment, vacuum drying and calcination processes are repeated. Finally, it is put into a carrageenan-styrene composite porous resin suspension, stirred for 2-4 hours, and vacuum dried at 60°C for 2-4 hours to obtain a hydrogenation catalyst protective agent.

9. The method for preparing a hydrogenation catalyst protective agent according to any one of claims 1 to 8, characterized in that: The hydrogenation catalyst protective agent comprises the following raw materials in parts by weight: 50 parts of a multi-stage pore oleophobic carrier, 60-100 parts of an active metal salt solution, 30-50 parts of an aqueous solution of a soluble salt of nickel oxide and / or copper oxide, and 100-150 parts of a carrageenan-styrene composite porous resin suspension.

10. The method for preparing a hydrogenation catalyst protective agent according to claim 9, characterized in that: The multi-level pore oleophobic carrier comprises the following raw materials in parts by weight: 100 parts of aluminum hydroxide powder, 5-15 parts of titanium sulfate powder, 5 parts of extrusion aid, 10-20 parts of active metal salt solution, 20-40 parts of pore expander, and 5-10 parts of aqueous solution of soluble salt of nickel oxide and / or copper oxide; the carrageenan-styrene composite porous resin suspension comprises the following raw materials in parts by weight: 40-60 parts of carrageenan-styrene composite porous resin and 60-90 parts of deionized water; wherein, the carrageenan-styrene composite porous resin comprises the following raw materials in parts by weight: 11 parts of carrageenan-styrene complex, 6 parts of dimethanol formal, 80 parts of 1,2-dichloroethane, and 4 parts of anhydrous FeCl3.

Citation Information

Patent Citations

  • Method for recycling waste hydrogenation catalyst

    CN105709853A

  • Honeycombed SCR (selective catalytic reduction) denitrification catalyst with three-dimensional hierarchical pore structure and preparation method thereof

    CN109731569A